2019
DOI: 10.1002/pts.2441
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and experimental verification of a drop test and compression test of a gable top package

Abstract: A finite element framework has been proposed that can be used to simulate both empty paperboard packages and package filled with plastic granulates. A gable top package was made of a commercial paperboard, and material properties needed in the material model were determined. Two simulations were performed, a drop test and a compression test. By comparison between experimental and numerical results, the deformation mechanisms at impact could be identified and correlated to material properties. When the package … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In principle, either the whole laminate can be modeled in a smeared manner with just one effective material model-see e.g. [195] for a recent application to modeling the drop test and compression test of a gable top package-or each of these layers can be described by the models presented in the previous section. In addition, several different materials are often applied that influence the overall performance of the laminate.…”
Section: Modeling Of Paperboard Laminatesmentioning
confidence: 99%
“…In principle, either the whole laminate can be modeled in a smeared manner with just one effective material model-see e.g. [195] for a recent application to modeling the drop test and compression test of a gable top package-or each of these layers can be described by the models presented in the previous section. In addition, several different materials are often applied that influence the overall performance of the laminate.…”
Section: Modeling Of Paperboard Laminatesmentioning
confidence: 99%
“…The box compression test (BCT) is perhaps the most common simulated load case. This test is routinely used to evaluate the stackability of a package, even if other load cases, such as drop tests, also occur in the literature 7 . A recent study on BCT of paperboard packages shows that it is possible to accurately predict the load–compression curve using a user‐friendly FE model and model the material as a homogeneous material 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Böröcz and Singh 5 measured the vibration levels that occur during parcel shipment by small delivery vehicles over ground transportation. Nygards et al 6 conducted a series of drop and compression tests on gable top packages and concluded that loading history has a large impact on the compression properties. Although these tests are as close as one can get to real conditions, they are costly and time‐consuming processes.…”
Section: Introductionmentioning
confidence: 99%